DIMENSI SISTEM MANAJEMEN LINGKUNGAN YANG DOMINAN TERHADAP UPAYA PRODUKSI BERSIH PERUSAHAAN ( STUDI KASUS INDUSTRI PENGOLAHAN KARET REMAH ) - Sawarni Hasibuan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
This study is designed to identify dimension of environmental management system that influence of cleaner production’s strategy accept and implementation at natural rubber industry, especially in crumb rubber industry. Factor Analysis technic with Principal Component is aplicated to extract that dimension, while correlation analysis is using to inference the influence that dimension with cleaner production performance. Based of existing condition, deviation of cleaner production performance from thecrumb rubber corporate’s enough big. Percentage of waste solid range 3 – 11 %, the corporate don’t treatment that waste because almost of waste solid use for landfill. Treatment of unpleasant odour from crumb rubber industry, i.e.: with scrubber at the smokestack after drying process, reengineering of pre-drying process, spray of volatile oil, and soak bokar with liquid smoke. Alternatives for waste water treatment i.e.: activated sludge system, chemical system, and aeration system.Principal Component analysis results 13 dimension, namely: internal communication, evaluation tools, environmental benefit, employee ability, professional team, incentive system, cleaner production centre, community consultation, regulation, operational policy, environmental investment, green consumer, and environment requisite. The correlation of that dimension with cleaner production performance at natural rubber industry is not good (rs < 0,5). The dimension has significant correlation are professional team, environment requisite, internal communication, evaluation tools, regulation, incentive system, and employee ability; while the others is not significant.